Water reclamation from palm oil mill effluent (POME): Recent technologies, by-product recovery, and challenges. (April 2023) - Mahmod, Safa Senan; Takriff, Mohd Sobri; AL-Rajabi, Maha Mohammad; Abdul, Peer Mohamed; Gunny, Ahmad Anas Nagoor; Silvamany, Hemavathi; Jahim, Jamaliah Md
Abstract: Water scarcity will continue to be a global challenge in the coming years as long as sustainable solutions remain far-fetched. It has become necessary to improve the efficiency of water circulation to reduce the net demand in high water consumption sectors such as agriculture. In palm oil industry, the extraction of crude palm oil from oil palm fruit bunch requires a large amount of water, half of which is discharged as palm oil mill effluent (POME) that is considered a high strength wastewater. The current trend of POME research focuses on moving from conventional open-ponding treatment to an integrated zero-discharge system for better effluent management. In this review, the attempts taken by researchers in laboratory and pilot scale were highlighted to achieve an effluent of high-quality water from POME that can be used as drinking water or recycled as boiler water in the palm oil production process. Membrane technology has recently emerged as one of the most promising separation techniques having a broad spectrum of applications including POME treatment. Furthermore, water reclamation technique involving evaporation can split POME solids and recover clean water in a more sustainable and space-saving manner. Additionally, recovery of by-product, such as biofertilizer and biofuels, is necessary to overcome the cost of the treatment. As a whole, in spite of several challenges, water reclamation from POME can be considered economically feasible system from techno-economic analysis perspective and it can feasibly shift the adopted industrial method from a linear take-use-discharge economy approach to a circular economy by keeping water in circulation. Graphical abstract: Unlabelled Image Highlights: Clean water could be reclaimed from POME through sustainable water management. Thermal, membrane and integrated zero-discharge treatment systems are discussed. Thermal treatment is less dependent on pre-treatment step. Efficient water reclamation could be achieved by integrated membrane separation. Biological treatment methods require long time, large area and high-cost.